2018
DOI: 10.1111/nph.15181
|View full text |Cite
|
Sign up to set email alerts
|

Cis‐directed cleavage and nonstoichiometric abundances of 21‐nucleotide reproductive phased small interfering RNAs in grasses

Abstract: Post-transcriptional gene silencing in plants results from independent activities of diverse small RNA types. In anthers of grasses, hundreds of loci yield noncoding RNAs that are processed into 21- and 24-nucleotide (nt) phased small interfering RNAs (phasiRNAs); these are triggered by miR2118 and miR2275. We characterized these 'reproductive phasiRNAs' from rice (Oryza sativa) panicles and anthers across seven developmental stages. Our computational analysis identified characteristics of the 21-nt reproducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 57 publications
5
69
0
Order By: Relevance
“…As observed for animal miRNAs (Chatterjee et al ., ; Tamim et al ., ), nonstoichiometric abundances at a PHAS locus may result from AGO loading and subsequent stabilization of functional siRNAs. At a given PHAS locus, some phasiRNAs are never observed in the sequenced sRNAs; we could extract these computationally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed for animal miRNAs (Chatterjee et al ., ; Tamim et al ., ), nonstoichiometric abundances at a PHAS locus may result from AGO loading and subsequent stabilization of functional siRNAs. At a given PHAS locus, some phasiRNAs are never observed in the sequenced sRNAs; we could extract these computationally.…”
Section: Resultsmentioning
confidence: 99%
“…Dukowic-Schulze et al (2016) reported that DNA methylation increased at 24-PHAS loci in maize meiocytes, and described a potential role in the regulation of chromosomal structure to promote normal meiosis. As reproductive phasiRNAs are extraordinarily abundant, cis methylation or even cis cleavage could result from nonspecific misloading of a small proportion into the 'wrong' AGO (Tamim et al, 2018). The pairing rules for 24-nt sRNAs and their targets is still unknown, that is, whether standard target prediction tools can be used that were built for 21-and 22-nt sRNAs.…”
mentioning
confidence: 99%
“…For instance, phasiRNAs are profusely produced during the reproductive stage, especially in the monocots and their subgroups of grasses (Xia et al, 2017)(Zhai et al, 2015). In rice there are >2000 PHAS loci generating 21-nt phasiRNAs and ∼400 loci 24-nt phasiRNAs (Tamim et al, 2018). Although phasiRNAs, including the well-known tasiRNAs, have been characterized in more and more plant species, there is no public online repository collecting reported or annotated phasiRNAs and provide convenient and quick access to this information.…”
Section: Discussionmentioning
confidence: 99%
“…In rice inflorescence, 828 and 35 of 21-and 24-PHAS were identified by Johnson et al [3], which could produce 21-and 24-nt phasiRNAs, respectively. In addition, 1136 and 1540 of 21-PHAS were identified in 93-11 and Nipponbare, respectively [9]. 70 and 34 of 24-PHAS were identified in 93-11 and Nipponbare by Song et al [16], respectively.…”
Section: Introductionmentioning
confidence: 95%
“…The genes encoding PIWI-interacting RNAs (piRNAs), which are a type of phasiRNAs, are required for producing mature sperm in animals [4]. In plants, phased siRNAs play a series of roles in abiotic and biotic stresses [5,6], seed germination [7] and reproductive development [3,[8][9][10]. Trans-acting siRNAs (ta-siRNAs) are a special class of phasiRNAs generated from TAS precursors (noncoding or coding transcripts), which silence targets in trans.…”
Section: Introductionmentioning
confidence: 99%